Enlarged memory T-cell pool and enhanced Th1-type responses in chronic myeloid leukemia patients who have successfully discontinued IFN-α monotherapy - Ilander, Mette; Kreutzman, Anna; Rohon, Peter; Melo, Teresa; Faber, Edgar; Porkka, Kimmo; Vakkila, Jukka; Mustjoki, Satu (PloS one, 2014)
A small proportion of chronic myeloid leukemia patients treated with interferon-α (IFN-α) monotherapy are able to discontinue the treatment without disease relapse although residual leukemia cells are present. Recently, we showed that these patients have increased amount of NK-cells and a distinct blood cytokine profile. We now aimed to study the function of NK- and T-cells in order to understand the role of the immune system in maintaining the treatment response after IFN-α discontinuation. The study included 13 patients: 5 patients were still treated with IFN-α monotherapy (IFN-ON, median treatment time 163 months) and 8 had stopped the treatment successfully (IFN-OFF, median time without therapy 42 months). Detailed immunophenotype and cytokine production of NK- and T-cells was analyzed with flow cytometry. In addition, the cytotoxicity of NK-cells was studied using K562 as target cells and both the degranulation and direct killing was measured. Compared to healthy controls, IFN-OFF patients had increased proportion of CD4(+) effector memory (CCR7(-)CD45RA(-); median 23% vs. healthy 16%, p = 0.009) and CD8(+) central memory T-cells (CCR7(+)CD45RA(-); median 26% vs. healthy 14%, p = 0.004). Further, upon stimulation the IFN-γ/TNF-α cytokine secretion by CD4(+) T-cells was significantly enhanced in IFN-OFF patients (median 13.7% vs. healthy 7.8%, p = 0.01), and CD4+ effector and central memory cells were the main cytokine producers. No similar increase was observed in IFN-ON group (6.5%). In addition, the proportion of NK-cells was significantly increased in IFN-OFF patients (median IFN-OFF 24%, healthy 13%, p = 0.04), but their direct killing of K562 cells was impaired. The cytotoxicity of NK-cells was also diminished in IFN-ON patients. To conclude, in addition to elevated NK-cell count, IFN-OFF patients have increased amount of memory T-cells, which are able to induce strong cytokine response upon stimulation. This activity may contribute to the maintenance of prolonged remission after successful IFN-α discontinuation.
Keywords: Th1 buňky; Humans; Interferon-alpha; lidé středního věku; CD4 Lymphocyte Count; Female; buňky K562; dospělí; imunologická paměť; lidé; buňky NK; Killer Cells, Natural; Adult; imunologické faktory; počet CD4 lymfocytů; ženské pohlaví; K562 Cells; Male; chronická myeloidní leukemie; Middle Aged; Th1 Cells; Immunologic Factors; interferon alfa; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; mužské pohlaví; Immunologic Memory